(3QSGdI RHOI GdEjeGfs - (3eMeO GdegOj GdbTdGbjs
(3ChdgG (B:s
(3GdMeO ddg GdPj JhMO HPGJg GdefRgI Yf GdMOhK hGdEecGf deG cGf Yde GdTQjYI GdPj gh eOGQ eMV ddSYGOI aj GdOGQjf efMUQG aj GdCUhd hGdaQhYs
(3BNQgG (B:s
(3jYfj Cf GdLRGA dGRe dcd Yed cd TNU dG jfbU Yfg eWdbG Ef NjQG aX hEf TQG addJYHjQ HGdPQI hdhbg JYGdi aj Mb GdTQjQ LRGA haGbG dcf bO jRGO Ydjg Ef cGf NjQG hWGYg Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds